16.8k views
1 vote
Solve the equation for m: 2m + 1 = -3m - 1

User BigTFromAZ
by
6.3k points

2 Answers

5 votes

The answer is:

m = -2/5

Work/explanation:

Combine like terms on each side:


\sf{2m+1=-3m-1}

Make sure all terms that contain m are on the left side and all constant terms are on the right. Don't forget to use the opposite sign when moving terms from one side to the other one.


\sf{2m+3m=-1-1}


\sf{5m=-2}

Divide each side by 5


\sf{m=-(2)/(5)}

Therefore, the answer is m = -2/5.

User Aryanknp
by
6.1k points
2 votes

Answer:

m =
(-2)/(5)

Explanation:

2m + 1 = -3m - 1 (Given)

2m + 1 + 1 = -3m - 1 + 1 (Addition Property of Equality)

2m + 2 = -3m (Simplify)

2m - 2m + 2 = -3m - 2m (Subtraction Property of Equality)

2 = -5m (Simplify)


(2)/(-5) = (-5m)/(-5) (Division Property of Equality)


(-2)/(5) = m (Simplify)

m =
(-2)/(5) (Symmetric Property of Equality)

User Leydi
by
5.9k points